2021
DOI: 10.12697/fce.2021.58.22
|View full text |Cite
|
Sign up to set email alerts
|

The main drivers for the occurrence of six red-listed epiphytic bryophytes and lichens in the boreo-nemoral forest landscape, Latvia

Abstract: Forest landscape plays a significant role in rare cryptogam distribution. However, data about the environmental demands of rare epiphytic bryophytes and lichens in boreo-nemoral forest landscapes are not complete. In this study, we focused on finding the main environmental predictors influencing the occurrence of three red-listed epiphytic bryophytes and three red-listed epiphytic lichens in the Latvian boreo-nemoral forest landscape. We obtained the records of species from the Natural Data Management System O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…In addition, the age parameters of phorophytes influence the species composition, abundance, and quantitative properties of the ELs [6,60,[62][63][64][65][66][67]. It was found that ELs are dependent on the DBH of the tree [5,66,[68][69][70][71][72]. Furthermore, the composition of the EL synusia on the same tree stem varies with height above the ground; in this case, the distribution of the ELs is determined not only by the physical features of the bark, but also by the environmental factors, such as light, humidity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the age parameters of phorophytes influence the species composition, abundance, and quantitative properties of the ELs [6,60,[62][63][64][65][66][67]. It was found that ELs are dependent on the DBH of the tree [5,66,[68][69][70][71][72]. Furthermore, the composition of the EL synusia on the same tree stem varies with height above the ground; in this case, the distribution of the ELs is determined not only by the physical features of the bark, but also by the environmental factors, such as light, humidity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of red-listed bryophyte species distribution in Latvia is related to forest habitats [11]. The studies about ecology of most of these species are missing, especially about red-listed liverworts.…”
Section: Introductionmentioning
confidence: 99%
“…Foi evidenciada uma relação positiva entre o diâmetro dos forófitos e a cobertura por epífitas avasculares, de acordo com o que era esperado (Frahm, 1990;Bates, 1992). O diâmetro da árvore suporte é considerado como um filtro importante para a a ocorrência deste grupo (Batista & Dos Santos, 2016), uma vez que há maior área superficial passível de colonização em forófitos com maiores diâmetros, assim como alta diversidade de microhabitats potencialmente favoráveis ao estabelecimento e sobrevivência das briófitas epífitas (Mežaka et al, 2008).…”
Section: Discussionunclassified